Prevalence of chronic insomnia in patients with obstructive sleep apnea - Stelzer,Fernando G. (2021)
Objectives: To investigate the prevalence of and factors associated with chronic insomnia and obstructive sleep apnea (CIOSA) comorbidity in obstructive sleep apnea (OSA) patients. Methods: Between March 2014 and March 2015, we conducted a prospective, cross-sectional study of 238 adults diagnosed with OSA according to polysomnography and International Classification of Sleep Disorders-Third Edition criteria. Results: The prevalence of CIOSA was 29%. There was a trend towards older age in the CIOSA group. Sex was not associated with CIOSA. Sleep-maintenance and sleep-onset insomnia predominated in the sample. Beck’s depression and anxiety inventory scores were higher in the CIOSA group. Both depression and anxiety symptoms were associated with CIOSA. The arousal and apnea-hypopnea indices were lower in the CIOSA group. CIOSA was also associated with age ≥ 60 years and current tobacco use. Severe OSA and alcohol use were negatively associated with CIOSA. Conclusions: Chronic insomnia is prevalent among OSA patients. Our study highlights the need for detailed evaluation of patients with sleep breathing disorders to diagnose other important sleep and mood disorders (such as depression and anxiety), given their frequent association.